2021
DOI: 10.30734/jpe.v8i1.1363
|View full text |Cite
|
Sign up to set email alerts
|

Modern Assessment dalam Menyongsong Pembelajaran Abad 21 dan Hambatan di Negara Berkembang

Abstract: This study aims to examine more deeply the 21st century learning associated with modern assessment and examine the obstacles faced by developing countries such as Indonesia. The research method used in writing this article is literature study. The analysis technique used in writing this article is content analysis. Quizizz also contains 21st century skills, which include critical thinking skills, creative and innovative skills, communication skills, and collaborative skills. Quizizz can increase motivation whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
0
9
1
4
Order By: Relevance
“…After giving treatments, the students score mean in posttest both experimental and control class have differences. It was opposite by the research finding which was conducted by previous study stated that Quizizz is perceived as having positive impact on students' engagement and learning outcomes (Handayani & Wulandari, 2021). In this research, The mean score of post test experimental class was 79.82 which were lower than the result of control class was 80.58. even though mean of post test experimental is lower than control class.…”
Section: Discussioncontrasting
confidence: 73%
“…After giving treatments, the students score mean in posttest both experimental and control class have differences. It was opposite by the research finding which was conducted by previous study stated that Quizizz is perceived as having positive impact on students' engagement and learning outcomes (Handayani & Wulandari, 2021). In this research, The mean score of post test experimental class was 79.82 which were lower than the result of control class was 80.58. even though mean of post test experimental is lower than control class.…”
Section: Discussioncontrasting
confidence: 73%
“…Cultivating anti-involution and critical thinking is essential in developing healthcare professionals, and exploring the relationship between them is vital in their training. Research indicates that both antiinvolution training and critical thinking are associated with innovative thinking (Handayani & Wulandari, 2021;Mu, 2021;Zeng, 2023). It can be shown that there is an indirect correlation between anti-involution training and critical thinking.…”
Section: Introductionmentioning
confidence: 99%
“…Some learning models that are often used include Project Based Learning (PJBL), Problem Based Learning, Skills Based Learning. These models must also increase student involvement in the learning process (Handayani & Wulandari, 2021). In this era, learning is no longer teacher-centered but rather student-centered, as is manifested in the independent learning curriculum.…”
Section: Introductionmentioning
confidence: 99%